Analisis Penilaian Kinerja Keuangan Perusahaan Menggunakan Rasio Keuangan Pada PT Unilever Indonesia Tbk Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Dedi Suhendro (Universitas Islam Negeri Sumatera Utara, 2018)
The purpose of this study to determine the financial performance of PT Unilever Indonesia Tbk 2010-2015 period. Financial ratios used: Liquidity Ratios, Asset Management Ratios, Debt Management Ratios and Profitability Ratios. The results of the research liquidity ratio, Current ratio and Quick Ratio decreased which indicates the liquidity of the company is not good and in fulfilling its smooth liability has not been said good. The ratio of asset management increases overall, because the company is already efficient in the use of assets to create sales that will increase the company's profit. The ratio of debt management, total debt to total assets is good enough because the company is able to cover its debt through its own capital and able to cover the interest expense with the funds owned. Profitability ratios show poor performance because the net profit of each sale is decreasing. Lack of efficiency in performance in optimizing their own capital to generate net income but using its assets productively increased so the profits derived by companies based on investments invested in the company is good enough.